2000
DOI: 10.1021/es001289n
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Origin of 1,2-Dichloropropane in an Unconfined Shallow Aquifer

Abstract: A shallow aquifer with different redox zones overlain by intensive agricultural activity was monitored for the occurrence of 1,2-dichloropropane (DCP) to assess the fate and origin of this pollutant. DCP was detected more frequently in groundwater samples collected in aerobic and nitrate-reducing zones than those collected from iron-reducing zones. Simulated DCP concentrations for groundwater entering an iron-reducing zone were calculated from a fate and transport model that included dispersion, sorption, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…Most of the contamination with 1,2-D has occurred in oxygen-limited or anaerobic subsurface environments, where reductive processes are more probable (17,34). In a previous study, the reductive dechlorination (i.e., hydrogenolysis) of 1,2-D to monochlorinated propanes and subsequent dehydrochlorination to propene was demonstrated in microcosms derived from river sediment (17).…”
mentioning
confidence: 98%
“…Most of the contamination with 1,2-D has occurred in oxygen-limited or anaerobic subsurface environments, where reductive processes are more probable (17,34). In a previous study, the reductive dechlorination (i.e., hydrogenolysis) of 1,2-D to monochlorinated propanes and subsequent dehydrochlorination to propene was demonstrated in microcosms derived from river sediment (17).…”
mentioning
confidence: 98%
“…The half-life of 1,3-DCPrpE in soil treated with manure was only 0.5 d (Dungan et al 2001). In sediments, evidence for 1,2-DCPrpA degradation was observed in an iron-reducing zone of an aquifer contaminated by agricultural activity (Tesoriero et al 2001). The field evidence indicated that no degradation was occurring in aerobic or denitrifying zones.…”
Section: Degradation Of Chloropropanoids In the Environmentmentioning
confidence: 96%
“…For example, Burow et al (1999) used data on the occurrence of DBCP and two of its transformation products to examine the relative importance of physical and chemical processes in controlling the fate of the fumigant in groundwater. Tesoriero et al (2001) employed a combination of field and laboratory studies to demonstrate the importance of redox conditions in controlling the fate of another fumigant, 1,2-dichloropropane, in groundwater ( Figure 19). Data on the occurrence of atrazine and DEA (also abbreviated as 'CIAT' by some authors; e.g., Erickson and Lee, 1989) in surface and groundwaters across the United States have provided persuasive evidence that the 'DEA fraction' (i.e., the molar proportion of atrazine-derived compounds that is present in a given environmental medium as DEA) increases with increasing residence time in the vadose zone (Barbash and Kolpin, 2010).…”
Section: Occurrence Of Pesticide Transformation Products In the Hydromentioning
confidence: 99%